Pengembangan Bahan Ajar Pada Materi Sebaran Barang Tambang Di Indonesia Mata Pelajaran Ips Terpadu Kelas VII SMP - Pertiwi, Sofita Gian; , Dr. Suharjo,M.S (2016)
This study aims to determine the criteria needs of teaching materials, teaching materials and effective models of teaching materials on the theme of the distribution of minerals in Indonesia are carried out in SMP Negeri 2 Wonosari. Research using descriptive research method qualitative and descriptive statistics. Development of teaching materials using the procedures of research and development (Research and Development) model of Dick & Carey (2001). Methods of data collection using observation, interviews, and questionnaires. The research instruments include a questionnaire kebutuham students and teachers, subject matter experts and design experts as well as books in the form of the development of an assessment instrument development book. Validity matter for validation of student assessment instruments. Analysis of the data in this study using SPSS 21. Based on the results of research and discussion of the results obtained by the research and development of teaching materials showed very good results because it is seen that the experimental class obtained average value (mean) pretest 69.94 with a standard deviation of 9.1417 and after receiving treatment (products of the development of teaching materials) obtain an average value (mean) postest average of 86.17 with a standard deviation of 8.8812 indicates that the probability value (sig.) .000. Based on these results, we can conclude that the correlation between the pre-test and post-test related significantly since the probability value <0.05. Therefore the probability 0.000 <0.05, then H0 is rejected, which means the results of the pretest and post-test results are not the same or significantly different.